Body composition and fatty tissue distribution in women with various menstrual status - Agnieszka Dmitruk; Jan Czeczelewski; Jan Czeczelewski; Jolanta Golach; Urszula Parnicka (National Institute of Public Health - National Institute of Hygiene, 2018)
Background. Menopause, also referred to as climacterium, is a period of multiple changes in the structure and functions of a woman organism. Objective. Determination of differences in body composition and fatty tissue distribution in women from groups discriminated based on their menstrual status. Material and Methods. The survey covered 312 women aged 38-75 years. Menstrual status of the surveyed women was established according to WHO guidelines based on answers to a questionnaire, and three groups were discriminated: women in the premenopausal period (group 1), in the perimenopausal period (group 2), and in the postmenopausal period (group 3). The following anthropomological measurements were taken: body height, body mass, waist and hip circumference, and thickness of 6 skinfolds. Their results enabled evaluating the somatic built of women in the separated groups. Fatty tissue distribution was determined based on TER distribution index calculated as a ratio of the sum of trunk skinfolds (TSS) to the sum of extremity skinfolds (ESS). Body composition of the women, including percentage of body fat, lean body mass, soft tissue mass, and total body water, was assessed using an IOI 353 analyzer by JAWON MEDICAL. In addition, percentages of women with underweight, normal content of fatty tissue, and these with overweight and obesity were calculated. The WHR index was computed in the case of obese women. Results. The highest values of body mass, hip circumference and most of the skinfolds were determined in the perimenopausal group, whereas the postmenopausal women were characterized by the highest percentage of body fat (PBF) and by the lowest contents of lean tissue, soft tissue, and total water content in the body. The highest percentage of obese women was found in the postmenopausal group, including 40% of them having visceral type obesity. The occurrence of the menopause contributed to changes in fatty tissue distribution, causing its shift from extremities toward the trunk. Conclusions. The study showed differences in the somatic built and body composition in groups of women distinguished based on their menstrual status.